Clomiphene citrate effect on testosterone level and semen parameters in 18 infertile men with low testosterone level and normal/low gonadotropines level. (July 2019) - Surbone, A.; Vaucher, L.; Primi, M.-P.; Leyvraz, C.; Pitteloud, N.; Ballabeni, P.; Mathevet, P.; Vulliemoz, N.
Abstract: Objective: To determine the effect of a 3-month course of clomiphene citrate (CC) on plasma testosterone (T) level and on semen parameters in 18 infertile men with low T level and normal or low gonadotropines level. Study design: A retrospective study was conducted by reviewing the medical records of men referred to a university fertility medicine unit for infertility management between January 2010 and March 2015. Men treated with CC for at least 3 months were included if they presented with: infertility plasma T level less than 11 nmol/l and low or normal FSH and LH levels sperm concentration >0.1 millions/ml. Results: 18 patients met the inclusion criteria. CC was prescribed for 3 months at the dose of 50 mg every 48 h. Plasma T level was assessed at baseline and after 1 month of CC administration. Semen parameters were assessed at baseline and after 3 months of CC administration. The median pre-treatment T level was 9.1 nmol/l; after 1 month of CC treatment the median post-treatment T level increased to 20.2 nmol/l (p = <0.001). Median baseline sperm concentration was 7 millions/ml with a median progressive motility of 18%. After 3 months of CC, the median post-treatment sperm concentration was 17.5 millions/ml (p = 0.024) and the median post-treatment progressive sperm motility was 18% (p = 0.40). Three natural pregnancies occurred during the treatment period. Conclusion: CC is an effective and inexpensive treatment to increase plasma T level in infertile men with low T level and normal or low gonadotropines level. Our study suggests that CC could increase sperm concentration even in oligospermic infertile men, without, however, a significant effect on progressive sperm motility. More powered randomized controlled trials are needed to definitively assess CC effect on sperm parameters and on natural pregnancy rates.